2011
DOI: 10.1155/2011/674318
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Control of HIV Dynamic Using Embedding Method

Abstract: This present study proposes an optimal control problem, with the final goal of implementing an optimal treatment protocol which could maximize the survival time of patients and minimize the cost of drug utilizing a system of ordinary differential equations which describes the interaction of the immune system with the human immunodeficiency virus (HIV). Optimal control problem transfers into a modified problem in measure space using an embedding method in which the existence of optimal solution is guaranteed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Additionally, the HIV mathematical modeling has allowed the analysis of the dynamic behavior of the virus infection, which has helped to propose regulation strategies to diminish indirectly the viral concentration [9][10][11]. An increasing number of works in the literature deal with the HIV virus regulation via control approaches and reduced HIV models [12][13][14][15][16][17][18][19][20]. Kim et al [21] found through a bifurcation analysis the range of optimal constant drug dosing for the reverse transcription inhibitor and the protease inhibitor in order to achieve LTNP in HIV patients.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the HIV mathematical modeling has allowed the analysis of the dynamic behavior of the virus infection, which has helped to propose regulation strategies to diminish indirectly the viral concentration [9][10][11]. An increasing number of works in the literature deal with the HIV virus regulation via control approaches and reduced HIV models [12][13][14][15][16][17][18][19][20]. Kim et al [21] found through a bifurcation analysis the range of optimal constant drug dosing for the reverse transcription inhibitor and the protease inhibitor in order to achieve LTNP in HIV patients.…”
Section: Introductionmentioning
confidence: 99%